Case Report: Takotsubo Syndrome Induced by Severe Anaphylactic Reaction During Anesthesia Induction and Subsequent High-Dose Epinephrine Resuscitation - Wei, Jiaojiao; Zhang, Le; Ruan, Xia; He, Kai; Yu, Chunhua; Shen, Le (Frontiers in Cardiovascular Medicine, 2022)
Takotsubo syndrome (TTS) is a non-ischemic cardiomyopathy characterized by an acute reversible left ventricular dysfunction with typical apical ballooning, usually with subsequent complete recovery. Early diagnosis and prompt treatment are of great essence. Herein, we described a case of TTS, who was scheduled initially for laparoscopic endometrial cancer staging. The 69-year-old woman presented with cardiogenic shock induced by severe anaphylactic reaction to the antibiotics during anesthesia induction. CPR was implemented while several boluses of 1mg epinephrine was injected. After return of spontaneous circulation, a large number of orange peel-like rash appeared on the head, face, neck and trunk of the patient. Transesophageal echocardiography (TEE) revealed diffused decreased left ventricular systolic function. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) and intra-aortic balloon pump (IABP) was therefore applied in the intensive care unit. Biomarkers like cardiac troponin I (cTnI) subsequently decreased with cardiac insufficiency improved. Finally, the patient was discharged in good condition. This case demonstrates that TTS could be secondary to severe anaphylactic shock and exogenous catecholamines. With the consideration of the reversible condition and predictable recovery of TTS, early vigilance and advanced life support devices should be necessary.